Rancang Bangun Aplikasi Perhitungan Gaji Karyawan pada Koperasi Udara Jawa Timur - Kurniawan, Candra Dwi Putra; sulistiowati, sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: The Cooperative of Udara Jawa Timur is one of the cooperatives in Sidoarjo. Currently the allowance given to the achievements of the branch employees are always late. This is because the process of calculating the salaries of employees in the cooperative branch takes a long time. In that process requires a salary document that has been validated by the central cooperative. The salary document contains basic salary, allowances achievements, and special allowances. To obtain the allowances of achievement, first step is branch cooperative should send a list of bill document to the central cooperative. The process of sending documents from the bill of each cooperative branch takes a long time because of constrained problem of distance. So that the procedures that have been applied to the Cooperative Air East Java is causing delays in the process of managing employee performance allowance branches. To solve the problem then payroll calculation application can help cooperative centers to overcome these problems. Applications that have been made can handle the validation process, performance allowance calculation, discounts, other allowances, and the calculation of wages for employees of the central and branch employees. Cooperatives and cooperative central branch can be interconnected using this application so that the process of sending documents from cooperative to cooperative central branch can be removed and can overcome the problems that occurred the previous time. Based on the results of trials that have been done can be concluded that the application complies with the expected goals. The application has been able to calculate the allowance achievements and calculate the salary of each cooperative branch of the appropriate time.